2017
DOI: 10.1089/neu.2016.4457
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Mice Demonstrate a Distinct Pattern of Injury after Repetitive Mild Traumatic Brain Injury

Abstract: Recently, there has been increasing interest in outcomes after repetitive mild traumatic brain injury (rmTBI) (e.g., sports concussions). Although most of the scientific attention has focused on elite athlete populations, the sequelae of rmTBI in children and young adults have not been well studied. Prior TBI studies have suggested that developmental differences in response to injury, including differences in excitotoxicity and inflammation, could result in differences in functional and histopathological outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 34 publications
3
25
1
Order By: Relevance
“…Our findings are consistent with those in a model of repeat closed head injury, where memory deficits (measured by performance in the Morris Water Maze task) were more severe in adolescent mice compared to adults (Mannix et al, ). Our results in adult mice contrast with results from other adult weight‐drop models, though.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings are consistent with those in a model of repeat closed head injury, where memory deficits (measured by performance in the Morris Water Maze task) were more severe in adolescent mice compared to adults (Mannix et al, ). Our results in adult mice contrast with results from other adult weight‐drop models, though.…”
Section: Discussionsupporting
confidence: 91%
“…26,27 Our findings are consistent with those in a model of repeat closed head injury, where memory deficits (measured by performance in the Morris Water Maze task) were more severe in adolescent mice compared to adults. 37 Our results in adult mice contrast with results from other adult weight-drop models, though. In one study, there were deficits in novel object recognition that were present 3 days after injury and, although improving over time, were still present 28 days postinjury.…”
Section: Discussioncontrasting
confidence: 99%
“…We and others have shown that repeat insults after a mTBI worsen traumatic axonal injury and neurobehavioral deficits in adult and pediatric models ( Prins et al., 2010 ; Donovan et al., 2014 ; Fidan et al., 2016 ; Mannix et al., 2017 ; Yu et al., 2017 ). Consistent with this, our DTI data showed that rmTBI exacerbated the changes in FA and other diffusivity indices when compared to a single episode of mTBI.…”
Section: Discussionmentioning
confidence: 86%